2015
DOI: 10.1063/1.4930881
|View full text |Cite
|
Sign up to set email alerts
|

Polar asymmetry of La(1−δ)Al(1+δ)O3/SrTiO3 heterostructures probed by optical second harmonic generation

Abstract: By combining transport measurements and optical second harmonic generation, we have investigated heterostructures formed between crystalline thin films of LaAlO 3 , with varying stoichiometry and TiO 2-terminated SrTiO 3 (001) substrates. Optical second harmonic generation directly probes the polarity of these heterostructures, thus complementing the transport data. The stoichiometry and the growth temperature are found to be critical parameters for controlling both the interfacial conductivity and the heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In particular, our main focus is to show the indispensability of STEM for understanding the properties of complex oxide interfaces and what needs to be improved and developed in the future. We note other techniques including synchrotronbased x-ray spectroscopies [33][34][35][36][37] (such as x-ray absorptions, x-ray linear dichroism and x-ray magnetic circular dichroism) and nonlinear optics [38][39][40] (such as second harmonic generations) are also powerful tools to study complex oxide interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our main focus is to show the indispensability of STEM for understanding the properties of complex oxide interfaces and what needs to be improved and developed in the future. We note other techniques including synchrotronbased x-ray spectroscopies [33][34][35][36][37] (such as x-ray absorptions, x-ray linear dichroism and x-ray magnetic circular dichroism) and nonlinear optics [38][39][40] (such as second harmonic generations) are also powerful tools to study complex oxide interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…5(b) . This process is determined by the , where z the direction perpendicular to the interface, is the induced second-order polarization response, , is electric field of the incident photon and χ is the susceptibility tensor 71 , 72 . It is clear then, that this behavior is observed in materials without inversion symmetry, non centrosymmetric, hence, since ferro and piezo electrics require broken inversion symmetry, is an excellent method to probe ferroelectric materials.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [ 48 ], SHG has been deployed to study such interfaces, and the main result is shown in Figure 9 , where different batches of samples grown at different temperatures and with different chemical composition are compared. The signal of the samples grown at about 720 C is only slightly increasing in the Al-rich region of the diagram, while the other two groups show a much more pronounced increase.…”
Section: Non-standard Lao/sto Hetero-structuresmentioning
confidence: 99%